2017
DOI: 10.1016/j.btre.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Significance of fermentation process on biochemical properties of Phaseolus vulgaris (red beans)

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 24 publications
(25 reference statements)
1
21
0
Order By: Relevance
“…Apart from the incorporation of flours and/or powders of pulses in food formulations, current research trends are on the nutraceutical functionalities of pulses (Chávez‐Mendoza & Sánchez, ; Díaz‐Sánchez, Guajardo‐Flores, Serna Guerrero, Gutierrez‐Uribe, & Jacobo‐Velázquez, ; Jamdar, Deshpande, & Marathe, ; Jing et al., ) as influenced by different processing methods (López‐Martínez, Leyva‐López, Gutiérrez‐Grijalva, & Heredia, ) or, more specifically, bioactivity of peptides and hydrolysates (Carbonaro, Maselli, & Nucara, ; Luna‐Vital et al., ) as well as hydrolyzability of the proteins and related physicochemical characteristics (Ghribi et al., ; Jamdar et al., ; Torres, Rutherfurd, Muñoz, Peters, & Montoya, ; Worku & Sahu, ). Other studies involve in vitro starch digestion (Bhattarai, Dhital, Wu, Chen, & Gidley, ; Dhital, Bhattarai, Gorham, & Gidley, ; Edwards et al., ; Ma, Wang, Wang, Jane, & Du, ; Pallares Pallares et al., ; Rovalino‐Córdova, Fogliano, & Capuano, ).…”
Section: Toward Increased Utilization Of Pulses: Current Trendsmentioning
confidence: 99%
“…Apart from the incorporation of flours and/or powders of pulses in food formulations, current research trends are on the nutraceutical functionalities of pulses (Chávez‐Mendoza & Sánchez, ; Díaz‐Sánchez, Guajardo‐Flores, Serna Guerrero, Gutierrez‐Uribe, & Jacobo‐Velázquez, ; Jamdar, Deshpande, & Marathe, ; Jing et al., ) as influenced by different processing methods (López‐Martínez, Leyva‐López, Gutiérrez‐Grijalva, & Heredia, ) or, more specifically, bioactivity of peptides and hydrolysates (Carbonaro, Maselli, & Nucara, ; Luna‐Vital et al., ) as well as hydrolyzability of the proteins and related physicochemical characteristics (Ghribi et al., ; Jamdar et al., ; Torres, Rutherfurd, Muñoz, Peters, & Montoya, ; Worku & Sahu, ). Other studies involve in vitro starch digestion (Bhattarai, Dhital, Wu, Chen, & Gidley, ; Dhital, Bhattarai, Gorham, & Gidley, ; Edwards et al., ; Ma, Wang, Wang, Jane, & Du, ; Pallares Pallares et al., ; Rovalino‐Córdova, Fogliano, & Capuano, ).…”
Section: Toward Increased Utilization Of Pulses: Current Trendsmentioning
confidence: 99%
“…Similarly to resistant starch, the colonic fermentation of oligosaccharides is also responsible for the production of short-chain fatty acids, acetate, propionate and butyrate, related to several health benefits [33]. To control the flatulence and reduce the content of oligosaccharides in legumes, many populations, especially in Asia and Africa, consume fermented legumes as an interesting nutritive food alternative [34].…”
Section: Fructooligosaccharidesmentioning
confidence: 99%
“…The fermentation process on legume-based substrates can also influence the presence of various bioactive components, such as vitamins, natural phenolics, and bioactive peptides, [20] and it can promote the reduction of anti-nutritional factors, as oligosaccharides, allergenic proteins, proteinase inhibitors, and phytates, which limit their consumption and affect the digestibility and the bioavailability of nutrients. [21] Moreover, it was reported that the lactic fermentation of adzuki beans and lentils allowed the accumulation of γ-aminobutyric acid (GABA), a blood pressure regulator, [22,23] while cowpeas fermentation with Lactobacillus plantarum led to changes in phenolic composition and improved antioxidant activity. [24] The fermenting strain chosen for this work, Lactobacillus paracasei (LP) CBA L74, has already been studied in recent works by Gallo et al [25,26] and Salameh et al [27] for cereal-based substrate fermentation.…”
Section: Introductionmentioning
confidence: 99%